MAIN DIRECTIONS OF STATE REGULATION DEVELOPMENT OF RAIL TRANSPORT IN UKRAINE - V.V., Matviienko (Pressing Problems of Public Administration, 2016)
The goal, objectives and basic principles of government regulation of formation of rail transport servicesmarket are de ned in the article. The structure of vertically integrated management of rail in Ukraine is proposed.The problems of the domestic rail industry are investigated and the strategic directions of governmentregulation of rail transport in the conditions of globalization and integration processes are de ned.